Molecular cloning of the Harvey sarcoma virus circular DNA intermediates. II. Further structural analyses. - Chang, H W (1980)
Three species of unintegrated supercoiled Harvey sarcoma virus DNA (6.6, 6.0, and 5.4 kilobase pairs) have been molecularly cloned from Harvey sarcoma virus-infected cells. On the basis of restriction enzyme analyses, the 6.6- and 6.0-kilobase pair viral DNAs contain two and one copies, respectively, of a 650-base pair DNA segment which contains sequences present at the 3' and 5' termini of the viral genome. R-loop structures formed between Moloney leukemia virus RNA and the cloned Harvey sarcoma virus DNA indicated that about 500 base pairs of the 650-base pair repeating segment was complementary to the 3' end of the viral RNA. During amplification in the Escherichia coli host, some recombinants containing the 6.6- or the 6.0-kilobase pair Harvey sarcoma virus DNA insert acquired or lost the complete 650-base pair DNA segment. These changes occurred in both recA+ and recA- E. coli.